The effectiveness of the application of project based learning with video content toward students' interests and learning outcomes in graphic design printing subject - Muhammad Yusuf Farizi; Dwi Maryono; Febri Liantoni (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2020)
This study aims to find out the improvement and effectiveness of students' learning interests and learning outcomes in using project-based learning models in graphic design printing subjects. The method in this research uses a quantitative quasi-experimental design method. Data collection is done through questionnaires and pretest-posttest controls. The subjects in this study were class XI Multimedia 2 as experimental class and XI Multimedia 1 as control class. The results showed differences in students' learning interests and learning outcomes after using the project-based learning model. This is evidenced by the first hypothesis test using t-test in posttest result of 0.00 which means less than an error level of 0.05, so the conclusion of both classes has a significant difference. In the second hypothesis test using the N-Gain test on learning interests in the experimental class was greater than the control class (41.21 > 20.77). As well as the learning outcomes of the N-Gain (50.30 > 24.49). Therefore, it is concluded that there is an increase in students' interest and learning outcomes in the experimental class.